2013
DOI: 10.1111/ajt.12331
|View full text |Cite
|
Sign up to set email alerts
|

The Survival Benefit of Kidney Transplantation in Obese Patients

Abstract: Obese patients have a decreased risk of death on dialysis but an increased risk of death after transplantation, and may derive a lower survival benefit from transplantation. Using data from the United States between 1995 and 2007 and multivariate non-proportional hazards analyses we determined the relative risk of death in transplant recipients grouped by body mass index (BMI) compared to wait-listed candidates with the same BMI (n ¼ 208 498). One year after transplantation the survival benefit of transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
122
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(130 citation statements)
references
References 24 publications
5
122
0
3
Order By: Relevance
“…There has been limited examination of the association of obesity with access to medical care among patients with ESRD. We recently reported that the survival benefit from transplantation compared with treatment with dialysis in most obese patients is similar to that among nonobese patients, and therefore obesity alone should not exclude patients from consideration of transplantation (7).…”
Section: Introductionmentioning
confidence: 99%
“…There has been limited examination of the association of obesity with access to medical care among patients with ESRD. We recently reported that the survival benefit from transplantation compared with treatment with dialysis in most obese patients is similar to that among nonobese patients, and therefore obesity alone should not exclude patients from consideration of transplantation (7).…”
Section: Introductionmentioning
confidence: 99%
“…The survival benefit of renal transplantation over dialysis might be considered for these patients. Although studies performed over the past 2 decades report better clinical outcomes of kidney transplantation for mild obese patients, the survival advantage of transplantation over dialysis is still uncertain in these patients with morbid and extremely morbid obesity [30,31] . Fortunately, with the noted increase in the prevalence of obesity and extremely morbid obesity, some of the transplantation centers are currently accepting patients with higher BMI as potential candidates for renal transplantation.…”
Section: Renal Transplantation In Extremely Morbid Obese Patientsmentioning
confidence: 99%
“…This benefit of transplantation compared with long-term dialysis holds among obese recipients as well. Previous studies have shown a 50% risk reduction in death for obese patients who receive a kidney transplant (4,5).…”
mentioning
confidence: 99%